Mesenchymal stem cells therapy in Veterinary Medicine: useful for immune mediated disorders? - Dias, Inês Esteves (2020)
Mesenchymal Stem Cells (MSCs) are multipotent cells, with capacity for self-renewal and differentiation into tissues of mesodermal origin. These cells are possible therapeutic agents for autoimmune disorders, since they present remarkable immunomodulatory ability. The increase of immune-mediated diseases in veterinary medicine has led to a growing interest in the research of these disorders and their medical treatment. Conventional immunomodulatory drug therapy (such as glucocorticoids or cyclosporine) is associated with numerous side effects that limit its long-term use, leading to the need for developing new therapeutic strategies, which are more effective and safe. The aim of this study is to perform a critical review about the therapeutic potential of these cells in the treatment of some auto-immune disorders (canine atopic dermatitis, feline chronic gingivostomatitis, inflammatory bowel disease and feline asthma) compared with their conventional treatment. MSC-based therapy in autoimmune diseases has been showing that this approach can improve clinical signs or even cause remission in most animals, with the exception of canine atopic dermatitis in which no improvement was observed. Although MSCs present a promising future in the treatment of most of these disorders, the outcome variability in some clinical trials has led to the current controversy among authors regarding their efficacy. MSCs-based therapy is currently requiring a deeper and detailed analysis that allows its standardization and better adaptation to the intended therapeutic results, in order to overcome current limitations in future trials.